FIGURATIVE LANGUAGE IN BRUNO MARS LYRICS - Muziatun Muziatun; Fahria Malabar; Elvian Hanny Mitali (Indonesian EFL Journal, 2022)
Figurative language is a language style that is used in the story and has an effect to influence the readers or listeners (Buta et al., 2018; Harun, Yusuf, Karnafi, 2020). Figurative language is also used by people to communicate (Colston, 2015; Colston Gibbs, 2021; Colston O'Brien, 2000). In communication, people communicate with each other using various ways, such as by using songs (Van Thao, 2021; Ward, Price, Davis, Crowther, 2018). It is because in the song’s lyrics there are many figurative languages (Bram Avillanova, 2019; Yaito Termjai, 2021). Then from the songs, people could convey their feeling and their conditions. The purpose of this research is to analyze the type of figurative language using the theory from Leech cited in H.D Trisna (2016). There are seven types of figurative language are irony, hyperbola, metaphor, metonymy, litotes, smile, and personification. The method used in this study is qualitative, because this study focused in analyzing the written material in context, included song’s lyrics. The object of this research was Bruno Mars’ song lyrics. However, the research only chooses three songs to analyze, they were Grenade, Long distance, and Talking to the moon. The research conducted some the analysis through some steps: Identifying, classifying, and analyzing. The result of the study indicate there are three figurative language used by Bruno Mars song lyrics. They are hyperbola, simile, and personification.Keywords: figurative language, irony, hyperbola, metaphor, litotes, simile, and personification.